Language Acquisition: Classroom Language Acquisition for Preschool Students - Rosdiana Rosdiana (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2017)
This paper explained about the language acquisition of the preschool students. The language acquisition involved the mini research by using qualitative approach. The researcher did observation to TK. A Bintang Semesta and did case study to know the acquisition of classroom language in that school. The researcher also identified the process of children’ language acquisition and also identified the process of acquisition. In this paper also explain the relation of data in the field with expert opinion about language acquisition.Key words: language acquisition, classroom language, preschool students